Supply management and family business: A review and call for research. Issue 2 (March 2017) - Maloni, Michael J.; Hiatt, Mark S.; Astrachan, Joseph H.
Abstract: Family-owned enterprises dominate global business, generating 70–90% of the world's gross domestic product. Existing management research has validated that family businesses often behave differently than non-family businesses, primarily by focusing on idiosyncratic non-economic goals that are not typically assessed in traditional business research. Extant supply management literature has yet to investigate the influences of family business, thus overlooking a potential significant source of variation in our research as well as limiting our managerial relevance. The objective of this paper is to introduce supply management scholars to family business, including its prominence and unique characteristics. Applying socioemotional wealth as a theoretical lens, we develop a research agenda from existing supply management and family business literature by offering propositions for future research where family business influences may permeate contemporary supply management topics including strategic supply management, sourcing strategy, supplier relationships, sustainability, risk, and e-procurement. In doing so, we provide an initial foundation for supply management scholars to both incorporate family business effects into research and launch new research streams. This is one of the first papers to our knowledge that introduces the field of family business to supply management scholars. Highlights: Family businesses behave and perform differently than non-family businesses. Extant literature studying family influences on supply management is mostly void. We introduce supply management scholars to family business. We develop research propositions of family business influences on supply management.